Covid-19 and Its Impact on the Lives of Healthcare Practitioners - Rodrigues, Karen Simona; Besiashvili, Nino (Caucasus Journal of Health Sciences and Public Health, 2020)
Healthcare providers are one of the most important people struggling to wipe of this devastating Pandemic situation. So a survey was conducted to study the impact Covid-19 pandemic has caused to the doctors, nurses and other medical staff on the front line withCovid patients and in other specialities. A questionnaire survey was sent to 40 healthcare providers practising in Georgia, Iran, India, U.K and USA. Some from the front line, treating Covid-19 patients and some from other specialities. After informing them with the importance of the study, they were asked to fill the 8 close ended questions on the questionnaire. A research was made based on the data collected from the survey. From the data collected it was observed that Covid has made a huge impact on the lives of most of the practitioners. The ones who were directly involved with Covid patients faced mental stress, sleep deprivation. It made them feel very terrible watching the patients suffer. From the ones not directly involved with Covid patients, about 47% had Covid case or suspected case in their clinics. The patients directly treating corona patients have to either stay away from their family after the shift or have to isolate themselves after coming home inorder to protect their family. Most of the healthcare practitioners who are not treating corona patients felt very sad about it whereas about a few felt safe that there was no direct involvement. 57%of the practitioners showed no Covid symptoms and were never tested positive whereas about a few showed Covid symptoms and recovered. The intensive work drained health-care providers physically and emotionally. Health-care providers showed their resilience and the spirit of professional dedication to overcome difficulties. Comprehensive support should be provided to safeguard the wellbeing of health-care providers. Regular and intensive training for all healthcare providers is necessary to promote preparedness and efficacy in crisis management. The sacrifices and struggles the healthcare workers all over the world are going through, for the sake of serving the humanity, should always be acknowledged and honoured.